Pengaruh Penerapan Green Accounting, Environmental Disclosure, dan Material Flow Cost Accounting Terhadap Sustainable Development Goals: Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI - Yasa Silpiani Anugrah; Mumun Maemunah; Carolyn Lukita (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to examine the effect of Green Accounting, Environmental Disclosure and Material Flow Cost Accounting (MFCA) on Sustainable Development Goals (SDGS). The population utilized is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019 - 2023. The sampling technique used was purposive sampling, so that the sample amounted to 100 observations (20 companies for 5 years). The analysis technique utilized is the classic assumption test, multiple linear regression analysis. The results showed that green accounting and environmental disclosure have an effect on achieving SDGs, while MFCA has no influence on SDGs. This study has implications for manufacturing companies that implement green accounting by incurring environmental costs that will help improve the company's SDGs.